2018
DOI: 10.1002/mds.27395
|View full text |Cite
|
Sign up to set email alerts
|

Structural and metabolic brain correlates of apathy in Huntington's disease

Abstract: Our findings indicate that apathy in Huntington's disease is not exclusively a consequence of basal ganglia and related frontal-executive alterations. It is subserved by a complex cortico-subcortical network where critical reward and emotional-related prefrontal, temporal, and limbic nodes contribute strongly to its severity. This highlights the contribution of damage in regions other than the basal ganglia to the clinical expression of Huntington's disease. © 2018 International Parkinson and Movement Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…There is selective early degeneration of the indirect pathway at the level of the striatum compared with the direct pathway in HD, and apathy in HD has been correlated with altered resting‐state activity in a circuit centered on the dorsal striatum . Apathy in HD has also been correlated with amygdala atrophy and hypoperfusion . The amygdala is heavily involved in stimulus‐response learning, and there is evidence to suggest distinct neuronal groups are involved with learning from loss and reward …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is selective early degeneration of the indirect pathway at the level of the striatum compared with the direct pathway in HD, and apathy in HD has been correlated with altered resting‐state activity in a circuit centered on the dorsal striatum . Apathy in HD has also been correlated with amygdala atrophy and hypoperfusion . The amygdala is heavily involved in stimulus‐response learning, and there is evidence to suggest distinct neuronal groups are involved with learning from loss and reward …”
Section: Discussionmentioning
confidence: 99%
“…73 Apathy in HD has also been correlated with amygdala atrophy and hypoperfusion. 74 The amygdala is heavily involved in stimulus-response learning, and there is evidence to suggest distinct neuronal groups are involved with learning from loss and reward. 64,75,76 This work suggests that effort for reward (HD cases had slower reaction times at all levels of reward on the RRTT, despite correction for TMS) was abnormal in HD cases compared with controls, but this deficit did not mediate apathy.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia activation in the insula has been shown to be associated with neuronal loss in this area early in the disease ( Tai et al, 2007 ). Additionally degeneration of the insula, as well as frontal-striatal circuits has been associated with apathy severity scores in HD ( Martínez-Horta et al, 2018 ). Taken together, insular degeneration appears to be linked strongly with disease symptomology, and future work may look to use the MRI signal in the insula to track HD progression and symptom worsening.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an MRI-PET study found that in a sample of 40 patients with early stage HD, higher apathy severity was associated with lower grey matter volume in subcortical regions, temporal lobes, and anterior cingulate cortex, as well as lower brain glucose metabolism in the prefrontal cortex, temporal lobes, insula, and precuneus (S. Martinez-Horta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%